2016
DOI: 10.1097/brs.0000000000001851
|View full text |Cite
|
Sign up to set email alerts
|

Sex Life and Impact of Operative Intervention on Sex Life-related Pain in Degenerative Spinal Conditions

Abstract: Study Design This study is a Therapeutic Retrospective Cohort Study Objective This study aims to determine if sexual function is relevant for patients with SPS and DS and to determine the impact of operative intervention on sexual function for these patients. Summary of Background Data The benefits of non-operative versus operative treatment for patients with spinal stenosis (SPS), and degenerative spondylolisthesis (DS) with regards to sexual function are unknown. Methods Demographic, treatment, and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
9
1
1
Order By: Relevance
“…Horst et al [ 22 ] and Kwan et al [ 23 ] have observed a correlation between depression and sexual dysfunction, and although there was a negative correlation between depression and BSFI score in our study, the statistical significance was weak. Depression initially affects the sexual drive alone, and other factors are involved only after a long duration of chronic illness.…”
Section: Discussioncontrasting
confidence: 87%
“…Horst et al [ 22 ] and Kwan et al [ 23 ] have observed a correlation between depression and sexual dysfunction, and although there was a negative correlation between depression and BSFI score in our study, the statistical significance was weak. Depression initially affects the sexual drive alone, and other factors are involved only after a long duration of chronic illness.…”
Section: Discussioncontrasting
confidence: 87%
“…The percentage of non-responders was relatively low (11.05%), fewer than the 47.69% found in chronic LBP patients17 ) , but higher than the 3% found for surgical patients6, 27 ) , showing that a relevant difference between different samples exists. By analyzing the characteristics of patients who did not respond to ODI-8, the odds were significantly higher in those over 60, females, unmarried patients, and in subjects with difficulties in walking and high pain intensity.…”
Section: Discussionmentioning
confidence: 74%
“…In a psychosocial model27, 29 ) , clinicians should consider sexual disability in the assessment and management of LBP, both in surgical and in conservative settings7 ) . Clinicians may explain which positions are more inclined to generate pain and which are more comfortable for sexual activity3 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Selain itu, adanya penyakit pada ibu, dalam hal ini prolaps uteri, juga merubah body image pasien yang mempengaruhi psikologi mengenai seksualitasnya (Pangastuti, 2019). Hal ini karena baik terapi operatif maupun non-operatif pada pasien prolaps uteri bukan bertujuan untuk memperbaiki fungsi seksual tetapi memperbaiki kondisi fisiknya (Horst at al, 2017).…”
Section: Pembahasanunclassified